A study on complementary resistive switching charateristics in resistive random access memory for next-generation non-volatile memory technology - Zhang, Haizhong (2017)
Resistive random access memory (RRAM) has shown the potential to become the future universal memory. The novel concept of complementary resistive switching (CRS) provides the promise of a high-density, selector-less RRAM crossbar array implementation, free of the sneak-path current problem. CRS behavior in HfOx-based RRAM device, using fully compatible materials with current mainstream CMOS technology, was investigated systematically in terms of physical switching mechanism, current conduction mechanism, self-compliance set-switching mechanism, CRS stability, and engineering method to improve CRS voltage window and read margin for the implementation of high-performance RRAM devices with stable and reliable CRS.